Energy balance in the watershed of Ipê, Northwestern São Paulo State, Brazil - Feitosa, Diego G. [UNESP]; Hernandez, Fernando B. T. [UNESP]; Franco, Renato A. M. [UNESP]; Teixeira, Antonio H. C.; Neale, Christopher M. (SPIE, the international society for optics and photonics, 2016)
The region of Ilha Solteira, in the Northwestern of São Paulo State, has been undergoing significant changes in agricultural land use and cover since 2006, as pasture fields have been replaced by sugarcane crop. This drastic change can lead to a disturbance in the energy balance, affecting the local climate. The aim of this paper was to assess some parameters related to the energy balance of Ipê's watershed, that changed since no sugarcane cultivation in 2006 to 2,164 hectares in 2011, occupying 31% of the catchment area with this important energy crop for the economy and the environment of Brazil. This study was carried out using remote sensing combined with weather data and using the SAFER (Simple Algorithm for Retrieving Evapotranspiration) model applied in 9 Landsat images collected between 2003 and 2011. The results showed a wide variation between the components of energy balance and when considering only the sugarcane crop were verified the increase values of ETa (Actual Evapotranspiration), H/Rn (Sensible Heat Flux/Net Radiation), TS (Surface Temperature), Rl↑ (Emitted longwave), Rl↓ (Incidente longwave) and surface albedo after the sugarcane production over these years. On the other hand, the NDVI, λE/Rn (Latent Heat Flux/Net Radiation) and Rn values (data) decreased in the same period. Also there was satisfactory correlation between NDVI and ETa. The SAFER model showed satisfactory results for studies of energy balance applied in the Northwestern of São Paulo State.
Keywords: Latent heat flux; Net radiation; Sensible heat flux; Sugar cane